Markedly long pause due to sinus arrest during dexmedetomidine use and nasal continuous positive airway pressure in two infants with respiratory syncytial virus infection. Issue 1 (January 2021) - Kojima, Hideo; Tanaka, Risa; Iwamoto, Yoichi; Ishido, Hirotaka; Sakurai, Yoshio; Masutani, Satoshi
Abstract: Nasal respiratory support for infants with respiratory distress caused by respiratory syncytial (RS) virus infection sometimes requires appropriate sedation. Dexmedetomidine can be an alternative sedative because of its advantage of less frequent respiratory suppression. We report the cases of twin infants with RS virus infection who showed unreported long pauses (4 and 10 s) due to sinus arrest while receiving dexmedetomidine. After termination of dexmedetomidine administration, the long pause of >2 s was no longer observed in both cases. RS virus infection may inhibit the conduction system and sometimes induce bradyarrhythmia. Cardiac and sinus arrests are reported as complications of dexmedetomidine administration. Thus, because dexmedetomidine administration and RS virus infection may additively or synergistically inhibit the conduction system, the use of dexmedetomidine in infantile RS infection should be carefully considered. If sedation is unavoidable, other drugs should be used first. An evidence-based safe regimen for sedation in infants with RS infection should be established in the near future. <Learning objective: Dexmedetomidine use as a sedative should be carefully considered in infants with respiratory syncytial (RS) infection because dexmedetomidine administration and RS virus infection may additively or synergistically inhibit the conduction system. If sedation is unavoidable, other drugs should be used first.>